Psychology and culture: the politics of recognition - Eefke Beyers (Acta Academica)
In chis article it is suggested that the cwo main ontological assumptions prevalent in mainstream Western psychology (acomism and holism) are accompanied by implicit moral ideals as well as concomitant constructions of selves, notions of good and political directives. A case is made for viewing present trends in psychology cowards the accommodation of culture as representative of a holistic ideal and of a concomitant politics of recognition of difference. This ontological and political perspective may be seen as a corrective of atomistic liberalism in the direction communitarian liberalism. The latter position is neither collectivise nor ethnocentric in orientation but liberal in the original sense of the word.